Real-world effectiveness of natalizumab treatment in patients with relapsing multiple sclerosis in Argentina and Chile - Ysrraelit, Maria Celica; Caride, Alejandro; Sinay, Vladimiro; Kindel, Mario Rivera; Halfon, Mario Javier; Patrucco, Liliana; Piedrabuena, Raul; Aragunde, Vanina Eleonor Diaz (Arquivos de Neuro-Psiquiatria, 2021)
Background: The real-world effectiveness of natalizumab in people with relapsing multiple sclerosis (PwRMS) in Argentina and Chile has not been reported. Objective: To evaluate the effectiveness of natalizumab treatment in PwRMS in Argentina and Chile, in clinical practice. Methods: We conducted a multicenter retrospective and observational study. We reviewed the medical records of PwRMS who had been treated with natalizumab for at least one year, without any interruption in MS treatment that lasted more than 12 weeks. We analyzed changes in annualized relapse rate (ARR), Expanded Disability Status Scale (EDSS) score and magnetic resonance imaging (MRI). Results: We enrolled 117 PwRMS treated with natalizumab. Natalizumab treatment was associated with a significant reduction in ARR from baseline after one year and two years of treatment (from 1.97 to 0.06 and 0.09 respectively; p<0.01 at each time point). From baseline, EDSS scores were reduced by 0.71 and 0.73 points at one and two years, respectively (p<0.01). No worsening of disability was observed in 82.9 and 67.5% of PwRMS at one and two years, respectively. The improvement in disability was 44.4% at one year and 39.3% at two years. During natalizumab treatment, the number of relapse-related hospitalizations was significantly reduced (p<0.01). MRI lesions (new/enlarging T2 or gadolinium-enhancing) were significantly reduced, compared with baseline. No evidence of disease activity was observed in 65% at two years of natalizumab treatment. Conclusions: Natalizumab significantly reduced disease activity in PwRMS in Argentina and Chile, in clinical practice. Natalizumab also decreased the number of hospitalizations compared with pre-natalizumab treatment.
Keywords: Observational Study; Effectiveness; Multiple Sclerosis; Natalizumab; Latin America